ACCOUNTABILITY AND TRANSPARENCY IN THE NONPROFITS: EVIDENCE FROM ONLINE CROWDFUNDING DURING COVID-19 PANDEMIC - Santos, M.; Dias, R. (EMAN 2021 Conference Proceedings, 2021)
Through accountability, organizations provide key information for stakeholders enabling the latter to make an informed assessment of organizational performance. To achieve transparency, organizations must make information accessible and timely. During crisis, as in the COVID-19 pandemic period, accurate accountability and transparency practices are most necessary so stakeholders can take informed decisions in an ongoing complex emergency. This study uses data available in an online crowdfunding platform to investigate in what extent are nonprofits implementing accountability and transparency policies regarding applications for funds published during the COVID-19 pandemic. A case study methodology is applied for providing evidence that nonprofits are not timely implementing transparency policies regarding fundraising campaigns. Nevertheless, results identify, in some cases, innovative accountability practices which impact in funds raised must further be analysed. These findings open up further investigations on the accountability of nonprofits during crisis and on the online organizational transparency regarding fundraising.